Pengembangan SIPORSI (Sistem Pelaporan Terintegrasi) Berbasis Google Spreadsheet untuk Pencatatan dan Pelaporan Kasus Tuberkulosis di Puskesmas Pembantu Kelurahan Serangan - Wirabuana Putra, Gede; Pradnyani, Putu Erma; Harjana, Ngakan Putu Anom; Sunardiana, I Wayan Agus (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2026)
Background: Puskesmas Pembantu (Pustu) Kelurahan Serangan lacks structured TB case recording and reporting mechanisms, relying on manual registers and informal WhatsApp reporting, causing data inconsistency and reporting delays. Objective: To design Integrated Reporting System (SIPORSI) (based on Google Spreadsheet suitable for TB case recording and reporting at Pustu Kelurahan Serangan. Methods: Research and Development approach using ADDIE model conducted from March to December 2024. Six healthcare workers were selected using purposive sampling. Data collection through semi-structured interviews, document analysis, and infrastructure identification. Qualitative analysis with thematic approach was used. Results: SIPORSI was successfully developed using ADDIE model. Analysis phase identified inadequate existing system, documentation gaps, high loss to follow up (37.5%), and low contact investigation (25%). Design and Development phases produced user-centered system with automatic validation and role-based access control integrated with national SITB. Implementation through structured training showed competency improvement of 33.3% (SIPORSI Knowledge domain: 66.7%). Evaluation demonstrated significant improvements: data quality (+31.8%), time efficiency (70.9%), SUS score (85.7/"Excellent"), loss to follow up reduction (37.5% to 8.3%), contact investigation increase (25% to 91.7%), and 100% reporting timeliness. Conclusion:  SIPORSI has proven to be an effective evidence-based solution in addressing TB recording system fragmentation in primary healthcare facilities through combination of accessible cloud-based technology, user-centered design, and structured training. The system has great potential for replication in other auxiliary health centers as a contribution to achieving Indonesia's TB elimination target by 2030.